Development of Self Regulated Learning Model in Studying Nursing (SRLSN) to Improve Student Learning Competence - Pepin Nahariani; Nursalam Nursalam; Mira Triharini; Ririn Probowati (Universitas Airlangga, 2013)
Introduction: New students at the college have to adjust to the learning process in a way more independent, not dependent on the lecturer, and self-regulation in learning. The purpose of this study is to develop a model of competence SRLSN to increased achievement among undergraduate students in the fourth semester of nursing STIKES Pemkab Jombang.Methods: The design used is explanatory and quasi-experimental pre-post test with control group. The population in this study were 71 nursing students of 4th semester of the academic year 2012–2013. The sample used 60 students with simple random sampling. Data was collected using focus group discussions, observation and questionnaires, then analyzed using regression results.Results: The results showed that the correlation between SRLSN preparation phase and implementation phase of 0.976, the correlation between the phase and the implementation phase has a self-reflection of 0.374, the relationship between the phase of preparation and reflection phase of 0.576. There are significant differences between treatment and control groups on aspects of cognitive competence achievement, competence affective, and psychomotor competencies.Discussion: SRLSN models are systematically formed by the preparation, implementation and reflection phase. The application of the model SRLSN will enhance student learning in the cognitive, affective, and psychomotor in achieving competence. Psychomotor competency has a value greater signi fi cance than other competencies. SRLSN models should be generalized to all learning processes, especially in nursing students.